Can Translation Studies become a transdiscipline? A survey of some theoretical problems related to its field of research - Pérez Durán, Gabriel (Cadernos de Literatura Comparada (teste), 2017)
The present study attempts to outline the scope of Translation Studies (TS) as a particularly complex field of research. Thus, this paper explores TS as a transdiscipline, regarding translation phenomena as probabilistic, not categorical phenomena. It seeks to establish the strategies that can help us to understand the transversal complexity of translation phenomena, in order to give TS a metatranslation space. It is an attempt to demonstrate that the approach to this complex research field needs transdisciplinary research strategies, including both human sciences and natural sciences. Going further, the present study overcomes the traditional division between both sciences and incorporates models such as the Third Culture (Schrödinger 1951, Snow 1959 and Brockman 1996). This study attempts to take the challenge of providing TS with an epistémé (Nouss 1995), conceived as a mental laboratory that puts in practice a family of different theories, each one with a limited scope of action. These theories will compose a complete description of the logical ways of the translatological function in society by exploring the transduction of cultural phenomena in society.